2017
DOI: 10.1111/cdoe.12294
|View full text |Cite
|
Sign up to set email alerts
|

Oral health conceptual knowledge and its relationships with oral health outcomes: Findings from a Multi‐site Health Literacy Study

Abstract: Objectives In 2010, a health literacy instrument designed to measure oral health conceptual knowledge was introduced. This developmental work was limited in that it included a relatively small and homogeneous study population and few oral health measures against which to test concurrent validity. The purpose of the present investigation is to expand upon the earlier work by utilizing a larger study sample and additional outcome variables. Methods Data for this report came from the Multi-site Oral Health Lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 20 publications
8
48
1
6
Order By: Relevance
“…Though CMOHK was initially considered to measure only the oral health conceptual knowledge, recent studies have been able to support the contention that conceptual knowledge is, indeed, a construct of health literacy. In a recent study by Macek et al [ 20 ], it was reported that CMOHK scores were significantly associated with the scores of other health literacy instruments like the Rapid Estimate of Adult Literacy in Medicine (REALM) and Short-test of functional health literacy in adults (TOFHLA), thus confirming CMOHK’s validity. In the original study [ 22 ], the CMOHK scores were divided into the following three categories: poor (0–11), fair (12–14), and good (15–23).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Though CMOHK was initially considered to measure only the oral health conceptual knowledge, recent studies have been able to support the contention that conceptual knowledge is, indeed, a construct of health literacy. In a recent study by Macek et al [ 20 ], it was reported that CMOHK scores were significantly associated with the scores of other health literacy instruments like the Rapid Estimate of Adult Literacy in Medicine (REALM) and Short-test of functional health literacy in adults (TOFHLA), thus confirming CMOHK’s validity. In the original study [ 22 ], the CMOHK scores were divided into the following three categories: poor (0–11), fair (12–14), and good (15–23).…”
Section: Discussionmentioning
confidence: 81%
“…Several publications from the Carolina Oral Health Literacy (COHL) study [ 16 ], have highlighted the important role played by OHL in influencing health behaviors and health outcomes [ 16 19 ]. In a large cross-sectional survey conducted at two university-based dental clinics in the United States, Multi-site Oral Health Literacy Research Study (MOHLRS), reported that about one-fifth (18%) of the participants had “low” conceptual knowledge [ 20 ]. Ju et al [ 21 ] conducted an interventional study among Indigenous Australian adults, where context-specific oral health literacy intervention was successful in improving the oral health literacy-related outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…After exclusion of duplicates, 1,058 studies were screened based on title and abstract, and 67 of those had their full‐texts retrieved for further analysis. After reading the full‐texts, 25 studies met the inclusion criteria for the systematic review and were included in the qualitative analysis . Due to the high clinical and methodological heterogeneity among investigations, only three studies were included in the meta‐analysis .…”
Section: Resultsmentioning
confidence: 99%
“…Another client‐related factor is that parents with low SES may have lower oral health literacy than parents with high SES and consequently have limited potential to teach their children how to perform optimal dental care. In the matter of professional‐related factors, not all dental professionals may have the skills to promote oral health behaviour effectively among parents with low SES, or to solve the challenges associated with lower levels of oral health literacy . Concerning factors related to the organization of care, clear guidelines for oral health promotion and prevention are not yet available.…”
Section: Discussionmentioning
confidence: 99%